A potential global boundary stratotype section and point (GSSP) for the Tarentian Stage, Upper Pleistocene, from the Taranto area (Italy): Results and future perspectives. (5th October 2015) - Negri, Alessandra; Amorosi, Alessandro; Antonioli, Fabrizio; Bertini, Adele; Florindo, Fabio; Lurcock, Pontus C.; Marabini, Stefano; Mastronuzzi, Giuseppe; Regattieri, Eleonora; Rossi, Veronica; Scarponi, Daniele; Taviani, Marco; et al.
Abstract: We present new data collected at the Fronte composite section near Taranto, where the Upper Pleistocene marine sedimentary succession is continuously exposed. Above a fossiliferous calcarenite yielding the "Senegalese" fauna, and abundant Cladocora, the 230 Th/U age of which is consistent with Marine Isotope Stage (MIS) 5, a 6.25 m thick pelitic unit is characterized by lithologically homogeneous marine sediments in which stable oxygen isotope, micropaleontological and palynological analyses suggest a long and undisturbed sedimentary interval across the Marine Isotope Stage (MIS) 5.5 peak (plateau). High sedimentation rates and a successful paleomagnetic pilot study indicate the probability of locating brief chronostratigraphic events useful for correlation with both continental and marine successions elsewhere. These results show the composite section to be a very promising candidate in the search for the Upper Pleistocene global boundary stratotype section and point (GSSP).